Variasi Animasi Gerakan Menggunakan Edit Data BVH - Aidil Primasetya Armin; Fridy Mandita (Fountain of Informatics Journal, 2018)
The BVH data is composed of two parts, the first part detailing the hierarchy and the initial pose of the framework while the second part describes the data for each frame. This data contains the translation and rotation of each joint in the form of coordinates based on X, Y, and Z axes. This study demonstrates methods for modifying BVH data to obtain new movements. First choose the joint on the BVH data, then determine the coordinate point of the initial movement and the coordinate point of the joint end motion. Both select the coordinate point to be modified. The three selected points are rotated using a rotation matrix based on the X, Y, and Z axes. The results of the test will be displayed in the form of animated characters.